Thrombectomy stent supporting material and preparation process thereof

Through the tamper-removing stent support material designed with specific components, the problems of mechanical adaptation, drug controlled release, self-repair and controllable degradation in a dynamic physiological environment are solved, and the dynamic response, precise controlled release and structural stability of the material are achieved, improving the efficacy and safety of the implanted device.

CN120242171APending Publication Date: 2025-07-04XUANWU HOSPITAL OF CAPITAL UNIV OF MEDICAL SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510377315.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

Traditional biomedical materials cannot achieve mechanical adaptation, controlled drug release, self-repair and controllable degradation in dynamic physiological environments, resulting in limited efficacy and safety of implanted devices.

Method used

The combination of polysebasic glyceride prepolymer, dynamic covalent bond crosslinking agent, carboxylated nanodiamond and temperature-sensitive-photothermal double-responsive microspheres is used to prepare the truncated scaffold support material through low-temperature 3D printing technology to achieve dynamic response, precise controlled release and structural stability.

Benefits of technology

The material has the ability to repair micro-damage independently in the physiological environment, realizes the controlled time and space release of drugs, matches the clinical treatment time window, and degrades into biocompatible metabolites, reduces the need for secondary surgery, and improves the therapeutic effect and safety.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials, and discloses a thrombectomy stent support material and a preparation process thereof, the thrombectomy stent support material comprises the following components by mass: 60-70% of a polysebacic diglyceride prepolymer; 25-35% of a dynamic covalent bond cross-linking agent; 5%-10% of carboxylated nano-diamond; 3 to 5 percent of temperature-sensitive and photo-thermal dual-response microspheres; the dynamic covalent bond cross-linking agent is composed of 4-formyl phenylboronic acid and hexamethylenediamine according to a molar ratio of 1: (1-3); the microsphere is prepared from poly (N-isopropylacrylamide), a gold nanorod and a recombinant tissue type plasminogen activating agent, and by combining a low-temperature 3D printing technology, the material can form a complex bionic structure, the mechanical strength is dynamically adjusted along with the physiological environment after implantation, and the material is safely degraded after functions are completed. The material is suitable for the scenes of cardiovascular and cerebrovascular stents, bone repair instruments and the like, has treatment accuracy, manufacturing suitability and clinical safety, and solves the problems of non-degradability, sudden drug release, mechanical mismatch and the like of traditional implants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and particularly to a support material for a thrombectomy stent and a preparation process thereof. Background Art

[0002] Traditional biomedical materials face common problems of single function and insufficient adaptability to the dynamic physiological environment in clinical applications. Taking cardiovascular stents as an example, existing metal or polymer materials often rely on permanent implantation, require secondary surgery for removal, and cannot achieve the on-demand release of therapeutic drugs, which easily leads to the risks of restenosis or thrombosis; while bone repair materials can avoid secondary trauma through degradation, but their mechanical attenuation rate is difficult to match the growth cycle of new bone tissue, easily resulting in stress shielding or structural collapse.

[0003] In addition, conventional manufacturing processes (such as hot melt extrusion) are limited by the thermal sensitivity of materials, and it is difficult to form a bionic stent with both high-precision porous structure and functional gradient distribution. Moreover, the static crosslinked network lacks the self-healing ability for microdamage, and is prone to fracture due to fatigue accumulation after long-term implantation.

[0004] The cross-action of the above defects severely restricts the efficacy and safety of implant devices, and there is an urgent need to develop a new generation of biomaterial systems with dynamic response, precise controlled release, and structural stability. Summary of the Invention

[0005] Aiming at the deficiencies of the prior art, the present invention provides a support material for a thrombectomy stent and a preparation process thereof, which solves the problem that traditional biomaterials cannot simultaneously achieve mechanical adaptation, drug controlled release, self-healing, and controllable degradation in a dynamic physiological environment.

[0006] To achieve the above objectives, the present invention is realized through the following technical solutions: In the first aspect of the present invention, a support material for a thrombectomy stent is provided, which solves the technical problems of insufficient mechanical properties, uncontrollable degradation, and single function of existing degradable stent materials through the collaborative design of specific components.

[0007] By mass percentage, the support material for the thrombectomy stent includes the following components: 60 - 70% of polyglycerol sebacate prepolymer; 25 - 35% of a dynamic covalent bond crosslinking agent; 5 - 10% of carboxylated nanodiamond; 3 - 5% of thermosensitive-photothermal dual-responsive microspheres.

[0008] This material uses polyglycerol sebacate prepolymer as the core matrix, and its long-chain flexible structure provides initial plasticity for the material, and at the same time forms a reversible network with the dynamic covalent bond crosslinking agent.

[0009] The dynamic covalent crosslinking agent is composed of 4-formylphenylboronic acid and hexanediamine in a molar ratio of 1:1 to 3. The double bonds of the borate ester bond (B-O) and the Schiff base bond (C=N) act synergistically to endow the material with dynamic response ability: the borate ester bond is sensitive to acidic environment, and the Schiff base bond can be specifically cleaved by metalloproteinases (such as MMP-9) overexpressed in the thrombus microenvironment, thus realizing "acid / enzyme dual-channel triggered degradation". This mechanism enables the scaffold to degrade rapidly after thrombus clearance, avoiding long-term foreign body residues.

[0010] Carboxylated nanodiamonds are embedded in the dynamic network through hydrogen bonding between the surface carboxyl groups and the polymer chains. Its high hardness characteristics significantly improve the short-term support force of the scaffold. At the same time, the nanoscale dispersion avoids the mechanical failure caused by the aggregation of traditional fillers. In addition, the interface between the nanodiamond and the dynamic covalent bond is further strengthened by photocontrolled crosslinking to form a covalent anchoring structure, thus maintaining mechanical stability at the initial stage of degradation.

[0011] The innovative design of the thermosensitive-photothermal dual-responsive microspheres integrates the therapeutic function into the material system. The recombinant tissue plasminogen activator (rt-PA) loaded in the microsphere core is encapsulated with a high drug loading rate by the emulsion-solvent evaporation method, and its activity retention rate is ≥95%, ensuring the thrombolysis efficiency; the thermosensitive property of poly(N-isopropylacrylamide) (PNIPAM) enables the microspheres to trigger drug release at body temperature (37 °C), while the gold nanorods modified with thiol groups on the surface can absorb external light energy and convert it into heat energy, accelerating drug diffusion through the photothermal effect. This dual-responsive mechanism realizes the temporal coordination of "thrombus embedding-demand thrombolysis-timely degradation", breaking through the limitation of traditional stent passive thrombus removal.

[0012] Preferably, the number-average molecular weight of the polyglycerol sebacate prepolymer is 10,000 to 15,000.

[0013] Preferably, the particle size of the carboxylated nanodiamonds is 10 to 50 nm, and the surface carboxyl density is 5 to 10 μmol / g.

[0014] Preferably, the particle size of the thermosensitive-photothermal dual-responsive microspheres is 10 to 20 μm.

[0015] Preferably, in the thermosensitive-photothermal dual-responsive microspheres: The molecular weight of poly(N-isopropylacrylamide) is 50,000 to 100,000, accounting for 70 to 80% of the total mass of the microspheres; this molecular weight range ensures that the phase transition temperature (LCST) of PNIPAM is stable at 32 to 34 °C, forming a trigger threshold with the human body temperature (37 °C), enabling the microspheres to rapidly shrink through temperature response after implantation and release the internal drugs.

[0016] The aspect ratio of the gold nanorods is 3:1, the surface is modified with thiol groups, and it accounts for 5 to 8% of the total mass of the microspheres; The aspect ratio of 3:1 optimizes the surface plasmon resonance effect of gold nanorods in the near-infrared region (700 - 900 nm), resulting in a photothermal conversion efficiency of ≥85%. The surface mercapto groups (-SH) are connected to the PNIPAM chains through covalent bonds, preventing the migration or aggregation of gold nanorods within the microspheres and providing reaction sites for subsequent photo-controlled crosslinking.

[0017] The drug loading of recombinant tissue plasminogen activator is 20 - 25 wt%, and the activity is ≥95%.

[0018] Preferably, the temperature-sensitive and photothermal dual-responsive microspheres are prepared by the following steps: Step 1: Copolymerization of the temperature-sensitive and photothermal matrix 1. Dissolve poly(N-isopropylacrylamide) (PNIPAM, molecular weight 50,000 - 100,000) in chloroform to prepare an oil-phase solution with a concentration of 10 - 15 wt%. 2. Add gold nanorods modified with surface mercapto groups (aspect ratio 3:1), and control the addition amount to be 5 - 8 wt% of the total mass of the oil phase. 3. Under nitrogen protection, stir and react at 55 - 60 °C for 4 - 6 h to form covalent bond connections between the amino groups (-NH2) at the ends of the PNIPAM chains and the mercapto groups (-SH) on the surface of the gold nanorods, generating a temperature-sensitive and photothermal dual-responsive matrix.

[0019] Step 2: Emulsification - solvent evaporation for loading rt-PA 1. Dissolve recombinant tissue plasminogen activator (rt-PA, activity ≥95%) in deionized water to prepare an aqueous solution with a concentration of 1 - 2 mg / mL. 2. Mix the aqueous phase with the oil phase from Step 1 at a volume ratio of 3:1, and emulsify at 800 - 1000 rpm for 30 - 45 min under high-speed shearing to form a water / oil emulsion. 3. Transfer the emulsion to a rotary evaporator, control the rotation speed at 50 - 60 rpm, the temperature at 35 - 40 °C, and the pressure at 0.08 - 0.1 MPa, and evaporate chloroform for 1 - 2 h to solidify and form drug-loaded microspheres.

[0020] The second aspect of the present invention provides a preparation process for the stent support material described in the first aspect of the present invention, including the following steps: Step (1): Synthesis of dynamic covalent polymer 1. Raw material mixing: Mix the polyglycerol sebacate prepolymer (60 - 70%), 4-formylphenylboronic acid, and hexamethylenediamine (molar ratio 1:1 - 3) in a reaction vessel in proportion. 2. Reaction under nitrogen protection: Stir and react for 20 - 24 h under a nitrogen atmosphere at 60 - 65 °C to form a dynamic covalent network (coexistence of borate ester bonds and Schiff base bonds); 3. Nanodiamond dispersion: Add carboxylated nanodiamonds (5 - 10%) and disperse for 30 min at an ultrasonic frequency of 40 kHz and a power of 200 W to ensure uniform embedding of nanoparticles into the polymer matrix.

[0021] Step (2) Thermosensitive microsphere loading: 1. Microsphere incorporation: Add thermosensitive - photothermal dual - responsive microspheres (3 - 5%) to the polymer mixture in step (1); 2. Low - speed mixing: Control the stirring rate at 100 - 150 rpm and the time at 2 - 3 h to avoid microsphere breakage or drug leakage.

[0022] Step (3) Low - temperature 3D printing and forming: 1. Slurry extrusion: Cool the mixed slurry to 8 - 10 °C and extrude it through a low - temperature 3D printing nozzle (diameter 0.2 - 0.4 mm); 2. Structure regulation: According to the preset grid density (high - density area: line width 0.1 mm, spacing 0.2 mm; low - density area: line width 0.3 mm, spacing 0.5 mm), adjust the nozzle moving speed (high - density area: 5 - 8 mm / s, low - density area: 12 - 15 mm / s).

[0023] Step (4) Light - controlled gradient cross - linking: 1. Ultraviolet light irradiation: Use an ultraviolet light source with a wavelength of 360 - 370 nm and irradiate differentially by region: High - density area: intensity 50 - 60 mW / cm 2 , time 25 - 35 s; Low - density area: intensity 90 - 100 mW / cm 2 , time 55 - 65 s; 2. Cross - linking regulation: Adopt mild irradiation conditions in the high - density area to prevent brittleness caused by over - cross - linking; Enhance the cross - linking density in the low - density area through high - intensity / long - time irradiation to compensate for the mechanical strength of the structurally loose area.

[0024] Step (5) Biomimetic surface mineralization: 1. Mineralization solution preparation: Simulate body fluid components: Na + 140 - 145 mM, Ca2+ 2.4 - 2.6 mM, 0.08 - 0.12% of polyaspartic acid; 2. Mineralization treatment: Immerse the scaffold in the mineralization solution and oscillate it at a constant temperature of 37 °C (frequency 50 rpm) for 45 - 50 h to form a hydroxyapatite coating.

[0025] Post - treatment steps in step (6) 1. Humidity balance: Place the scaffold in an environment with a humidity of 85 - 95% and let it stand for 10 - 14 h to release internal residual stress; 2. Sterilization treatment: Sterilize it with ethylene oxide gas (concentration 600 - 800 mg / L) for 4 - 6 h to ensure sterility.

[0026] The present invention provides a support material for a thrombectomy stent and its preparation process. It has the following beneficial effects: Through the reversible bonding mechanism of the dynamic covalent network, the material of the present invention has the ability to autonomously repair micro - damages in the physiological environment. This characteristic can effectively extend the functional life of the implanted device, avoid sudden structural failure caused by local stress concentration or mechanical wear, and provide a reliable guarantee for long - term applications in dynamic physiological environments such as blood vessels and bone tissues.

[0027] Based on the photothermal - thermosensitive synergistic effect, the material of the present invention can respond to external stimuli (such as near - infrared light) to achieve spatiotemporally controllable drug release. This characteristic can match the time - window requirements of clinical treatment, release high - concentration drugs at the thrombus or tumor site, while reducing the risk of systemic exposure, and significantly improving the treatment effect and safety.

[0028] Through the biomimetic mineralized layer and the micro - nano topological structure adapted to cells, the present invention can guide the directional adhesion and proliferation of osteoblasts, endothelial cells, etc., and accelerate the functional regeneration of damaged tissues. This bioactive design not only shortens the rehabilitation period, but also reduces the rejection reaction between the implant and the host tissue, providing a new strategy for complex defect repair.

[0029] The low - temperature 3D printing technology of the present invention takes into account both the retention of the activity of the dynamic network and the high - precision forming ability, and supports the personalized customization of implanted devices with gradient mechanics and porous structures. This technology breaks through the limitations of traditional manufacturing processes on material design and provides a solution for the adaptation needs of special anatomical shapes in clinical practice.

[0030] The controllable degradation characteristic of the material of the present invention enables it to gradually degrade into biocompatible metabolites after completing functions such as support and drug delivery, and be excreted from the body through natural metabolic pathways. This characteristic completely eliminates the problem of the need for secondary surgery to remove traditional metal or polymer implants, reducing the physical and mental burden on patients. Detailed implementation manners

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention. Example 1

[0032] The allocation ratios of each group are as follows: Glycerol polysebacate prepolymer: 64%; Dynamic covalent bond crosslinking agent (4-formylphenylboronic acid:hexanediamine = 1:2): 28%; Carboxylated nanodiamond (particle size 30 nm, carboxyl density 8 μmol / g): 5%; Thermosensitive-photothermal dual-responsive microspheres (PNIPAM molecular weight 75,000, gold nanorod proportion 6%, rt-PA drug loading 22 wt%): 3%; The preparation steps are as follows: 1. Synthesis of dynamic covalent polymer: Mix the prepolymer, 4-formylphenylboronic acid (0.2 mol), and hexanediamine (0.4 mol), and react at 62 °C for 22 h under nitrogen protection; Add carboxylated nanodiamond and ultrasonically disperse (40 kHz, 220 W) for 35 min.

[0033] 2. Loading of thermosensitive microspheres: The microspheres are stirred and mixed into the polymer matrix at 120 rpm for 2.5 h.

[0034] 3. Low-temperature 3D printing: Cool the slurry to 9 °C, the nozzle diameter is 0.3 mm, the moving speed in the high-density area is 6 mm / s, and the low-density area is 13 mm / s.

[0035] 4. Light-controlled gradient crosslinking: Ultraviolet wavelength 365 nm, the intensity in the high-density area is 55 mW / cm 2 (30 s), and the low-density area is 95 mW / cm 2 (60 s).

[0036] 5. Biomimetic mineralization: Mineralize in the mineralization solution (Na + 142 mM, Ca 2+ 2.5 mM, polyaspartic acid 0.1%) for 48 h.

[0037] 6. Post-treatment: Static at 90% humidity for 12 h, sterilized with ethylene oxide (700 mg / L, 5 h). Example 2

[0038] The component ratios of each group are as follows: Glycerol polysebacate prepolymer: 60%; Dynamic covalent crosslinking agent (4-formylphenylboronic acid:hexamethylenediamine = 1:3): 32%; Carboxylated nanodiamond (particle size 50 nm, carboxyl density 5 μmol / g): 5%; Thermosensitive-photothermal dual-responsive microspheres (PNIPAM molecular weight 100,000, proportion of gold nanorods 8%, rt-PA drug loading 25 wt%): 3%; The preparation steps are as follows: 1. Synthesis of dynamic covalent polymer: The prepolymer and the crosslinking agent (0.15 mol of 4-formylphenylboronic acid, 0.45 mol of hexamethylenediamine) react at 60 °C for 24 h; The nanodiamond is ultrasonically dispersed (38 kHz, 200 W) for 40 min.

[0039] 2. Loading of thermosensitive microspheres: The microspheres are stirred and mixed at 150 rpm for 3 h.

[0040] 3. Low-temperature 3D printing: The slurry is cooled to 8 °C, the nozzle diameter is 0.2 mm, the moving speed in the high-density area is 5 mm / s, and the moving speed in the low-density area is 15 mm / s.

[0041] 4. Light-controlled gradient crosslinking: The ultraviolet wavelength is 370 nm, the intensity in the high-density area is 50 mW / cm 2 (35 s), and the intensity in the low-density area is 100 mW / cm 2 (65 s).

[0042] 5. Biomimetic mineralization: Mineralization solution (Na + 145 mM, Ca 2+ 2.6 mM, 0.12% of polyaspartic acid) for mineralization for 50 h.

[0043] 6. Post-treatment: Static at 95% humidity for 14 h, sterilized with ethylene oxide (800 mg / L, 6 h). Example 3

[0044] The component ratios of each group are as follows: Glycerol polysebacate prepolymer: 65%; Dynamic covalent bond crosslinker (4-formylphenylboronic acid:hexamethylenediamine = 1:1): 25%; Carboxylated nanodiamond (particle size 10 nm, carboxyl density 10 μmol / g): 7%; Thermosensitive-photothermal dual-responsive microspheres (PNIPAM molecular weight 50,000, proportion of gold nanorods 5%, rt-PA drug loading 20 wt%): 3%; The preparation steps are as follows: 1. Synthesis of dynamic covalent polymer: The prepolymer reacts with the crosslinker (0.25 mol of 4-formylphenylboronic acid and 0.25 mol of hexamethylenediamine) at 65 °C for 20 h; The nanodiamond is ultrasonically dispersed (45 kHz, 180 W) for 25 min.

[0045] 2. Loading of thermosensitive microspheres: The microspheres are stirred and mixed at 100 rpm for 2 h.

[0046] 3. Low-temperature 3D printing: The slurry is cooled to 10 °C, the nozzle diameter is 0.4 mm, the moving speed in the high-density area is 8 mm / s, and the low-density area is 12 mm / s.

[0047] 4. Light-controlled gradient crosslinking: The ultraviolet wavelength is 360 nm, the intensity in the high-density area is 60 mW / cm 2 (25 s), and the low-density area is 90 mW / cm 2 (55 s).

[0048] 5. Biomimetic mineralization: Mineralization solution (Na + 140 mM, Ca 2+ 2.4 mM, polyaspartic acid 0.08%) for 45 h of mineralization.

[0049] 6. Post-treatment: Static for 10 h at a humidity of 85%, and sterilized with ethylene oxide (600 mg / L, 4 h).

[0050] Comparative example 1: Compared with Example 1, the difference is that the dynamic covalent bond crosslinker (4-formylphenylboronic acid + hexamethylenediamine) is replaced with an equal amount of ordinary covalent crosslinker (glutaraldehyde), and the other components and process conditions are the same.

[0051] Comparative example 2: Compared with Example 1, the difference is that carboxylated nanodiamond is not added, and the other components and process conditions are the same.

[0052] Comparative Example 3: Compared with Example 1, the difference is that the ultraviolet light gradient irradiation is cancelled, and only a single intensity (80 mW / cm 2 ) is used for irradiation for 60 s, and the remaining process conditions are the same.

[0053] Comparative Example 4: Compared with Example 2, the difference is that gold nanorods are not added to the thermosensitive-photothermal dual-responsive microspheres, and the remaining components and process conditions are the same.

[0054] Comparative Example 5: Compared with Example 2, the difference is that polyaspartic acid is not added to the biomimetic mineralization solution, and the remaining components and process conditions are the same.

[0055] Comparative Example 6: Compared with Example 3, the difference is that the 3D printing temperature is adjusted to 25 °C, and the remaining process conditions are the same.

[0056] Comparative Example 7: Compared with Example 3, the difference is that the molar ratio of 4-formylphenylboronic acid to hexanediamine in the dynamic covalent crosslinking agent is adjusted to 1:4, and the remaining components and process conditions are the same.

[0057] Test Example 1: Purpose: To verify the effects of the dynamic covalent network, carboxylated nanodiamonds, and the molar ratio of dynamic bonds on the elastic modulus, degradation period, and degradation uniformity of the scaffold.

[0058] The experimental steps are as follows: 1. Sample preparation: Scaffold samples were prepared according to the formulations and processes of Examples 1-3 and Comparative Examples 1, 2, and 7 (n = 5 for each group).

[0059] Sample size: dumbbell shape (ASTM D638 standard, length 50 mm, gauge section 10 mm × 2 mm × 1 mm).

[0060] 2. Elastic modulus test: Using a universal material testing machine (Instron 5967), the sample was stretched at a rate of 5 mm / min, the stress-strain curve was recorded, and the initial elastic modulus was calculated.

[0061] Test conditions: Test after soaking in PBS solution at 37 °C for 24 h.

[0062] 3. Degradation period determination: The samples were immersed in a PBS buffer solution at 37 °C and pH 7.4 (containing 10 U / mL lipase), and the morphological changes were observed daily.

[0063] Define the degradation endpoint: The sample breaks or the mass loss ≥ 90%.

[0064] 4. Evaluation of degradation uniformity: Use a scanning electron microscope (SEM, Hitachi SU8000) to observe the pore distribution on the surface of the sample on the 5th day of degradation.

[0065] The experimental results are shown in Table 1: Table 1 Comparison of mechanical properties and degradation test results Group Elastic modulus (MPa) Degradation period (days) SEM observation (5th day of degradation) Key defect Example 1 12.3±1.2 11.2±0.8 Uniform pores (pore size 5 - 10 μm) None Example 2 14.5±0.9 9.8±1.1 Uniform pores (pore size 8 - 12 μm) None Example 3 16.1±1.5 13.5±1.3 Uniform pores (pore size 3 - 7 μm) None Control Example 1 18.6±2.1 >30 Smooth surface, no holes Cannot degrade, block blood vessels Control Example 2 8.2±0.7 6.5±0.5 Large pores aggregated (pore size 20 - 50 μm) Insufficient support force, premature collapse Control Example 7 13.9±1.8 4.2±0.3 Crack propagation (length ≥ 100 μm) Degrade too fast, risk of inflammation From the experimental data in Table 1, it can be obtained that: In this experiment, by comparing the mechanical and degradation behaviors of the examples and the comparative examples, the synergistic mechanism of the dynamic covalent network and the nano-reinforcing phase was revealed. The introduction of dynamic covalent bonds (borate bonds and Schiff base bonds) enables the scaffold to achieve controllable degradation through an acid / enzyme dual-channel in the physiological environment. The borate bonds preferentially break in a weakly acidic environment (such as pH 5.0 - 6.0 at the thrombus site), releasing prepolymer fragments; while the Schiff base bonds are gradually hydrolyzed under the action of proteases. The two regulate the degradation rate through a dynamic balance (the degradation period of Examples 1 - 3 is 8 - 14 days). In Comparative Example 1, the ordinary covalent bond (glutaraldehyde) lacks dynamic responsiveness, resulting in the inability of the scaffold to degrade (> 30 days), confirming the necessity of the dynamic bond design. In addition, the excessive molar ratio of the dynamic bond in Comparative Example 7 (1:4) breaks the degradation synergy of the acid / enzyme dual-channel, and the excessive proportion of Schiff base bonds causes out-of-control degradation in the acidic environment (4.2 days), further verifying the basis of the molar ratio (1:1 - 3).

[0066] The addition of carboxylated nanodiamonds significantly improves the mechanical properties of the scaffold (the elastic modulus of Examples 1 - 3 is 12.3 - 16.1 MPa) through the hydrogen bond and ionic interaction between its surface carboxyl groups and the polymer matrix. The uniform dispersion of nanoparticles (the pore size shown by SEM in Example 1 is 5 - 10 μm) not only enhances the network rigidity as physical cross-linking points but also inhibits the propagation of microcracks through interfacial stress transfer, thereby delaying the structural collapse during degradation. In Comparative Example 2, the scaffold without added nanodiamonds has a modulus that drops sharply to 8.2 MPa due to the lack of a reinforcing phase, and large pore aggregations (pore size 20 - 50 μm) appear during degradation, resulting in premature loss of mechanical properties. This indicates that the proportion of nanodiamonds (5 - 10%) is a key parameter for balancing mechanical strength and degradation uniformity.

[0067] The experimental data further show that the co - design of the dynamic network and the nano - enhanced phase realizes the precise regulation of the mechanical properties and degradation behavior of the scaffold. In the examples, the reversible fracture - recombination characteristics of the dynamic bonds (such as the inability to self - repair in Comparative Example 1) and the mechanical enhancement effect of the nanodiamonds work together to enable the scaffold to maintain sufficient supporting force (elastic modulus ≥ 12 MPa) at the initial stage of degradation, and rapidly degrade (8 - 14 days) after thrombolysis, avoiding the risk of long - term retention. In contrast, in Comparative Example 7, due to the imbalance of the dynamic bonds, the degradation is too fast (4.2 days), which cannot meet the time - window requirements (usually 7 - 10 days) of clinical temporary support materials. This result verifies the irreplaceability of the component parameters (dynamic bond type, molar ratio, nano - phase content) in the present invention from both positive and negative aspects.

[0068] Test Example 2: Objective: To verify the effects of the photo - controlled gradient cross - linked structure and the photothermal effect of gold nanorods on the drug release rate and controllability.

[0069] The experimental steps are as follows: 1. Sample preparation: Prepare drug - loaded scaffolds according to the formulations and processes of Examples 1 - 3 and Comparative Examples 3 (without photo - controlled gradient) and Comparative Example 4 (without gold nanorods) (n = 5 for each group).

[0070] Sample size: Cylindrical (diameter 5 mm, height 10 mm).

[0071] 2. Photothermal conversion efficiency test: Irradiate the surface of the sample with an 808 nm near - infrared laser (power density 1.5 W / cm 2 ), and an infrared thermal imager (FLIRA65) records the temperature rise curve within 10 min to calculate the photothermal efficiency.

[0072] 3. Drug release rate determination: Immerse the sample in 37°C PBS (pH 7.4) and divide it into two groups: Non - irradiation group: Test under light - avoiding conditions; Irradiation group: Apply an 808 nm laser (1.5 W / cm 2 , 5 min) every 2 h.

[0073] Use HPLC (Agilent 1260) to measure the cumulative release amount of rt - PA and calculate the thrombolysis efficiency within 24 h (compared with the activity of the standard product).

[0074] 4. Release controllability analysis: Compare the differences in release rates under light - irradiated and non - irradiated conditions.

[0075] The experimental results are shown in Table 2: Table 2 Comparison of Photothermal Response and Drug Release Test Results Group Photothermal temperature rise amplitude (ΔT, °C) Thrombolysis efficiency in 24 h (%) Release rate difference (ΔR, %) Key defect Example 1 8.7±0.9 87.5±3.2 41.3±4.1 None Example 2 9.2±1.1 85.0±2.8 38.5±3.7 None Example 3 7.9±0.8 82.4±4.0 35.6±5.2 None Control Example 3 8.1±1.0 91.2±2.5 8.4±1.3 Severe burst release (ΔR < 10%) Control Example 4 1.5±0.3 61.8±5.6 2.1±0.9 No photothermal response, release delay From the experimental data in Table 2, it can be obtained that: The photothermal conversion ability of gold nanorods is the core driving force for triggering the phase transition of thermosensitive microspheres: under near-infrared light irradiation, gold nanorods absorb light energy and convert it into heat energy (the temperature rise in Examples 1-3 is 7.9-9.2 °C), resulting in the contraction of the hydrophobic segments (isopropyl groups) of PNIPAM microspheres when the local temperature exceeds its lower critical solution temperature (LCST≈32 °C), thereby squeezing and releasing the encapsulated rt-PA. This process realizes the on-demand release of drugs through the photothermal-thermosensitive coupling effect. In Comparative Example 4, due to the lack of gold nanorods, no effective temperature rise can be generated (ΔT≤1.5 °C), and the drug release efficiency relying only on passive diffusion is significantly reduced (61.8%), verifying the necessity of photothermal agents in functional design.

[0076] The gradient cross-linked structure regulates the drug diffusion path through different cross-linking densities and is the key to inhibiting burst release. In the examples, the high-density cross-linked region forms a dense network barrier, restricting the swelling of microspheres under non-irradiated conditions and ensuring that rt-PA is slowly released only through the micropores on the surface of the microspheres (the release amount within 24 h≤15%); while the low-density region expands the pores through dynamic bond recombination after irradiation, accelerating drug diffusion. This light-controlled gradient design makes the difference in release rates (ΔR≥35%) significantly higher than that of Comparative Example 3 with homogeneous cross-linking (ΔR = 8.4%). In Comparative Example 3, due to the single cross-linking strength, no structural barrier can be formed, resulting in early burst release of drugs (the release amount within 24 h≥40%), proving the irreplaceability of gradient cross-linking for release controllability.

[0077] The photothermal-gradient synergistic effect further optimizes clinical applicability. The controllable temperature rise range (7.9-9.2 °C) avoids overheating damage to surrounding tissues. At the same time, the gradient cross-linking endows the stent with mechanical adaptability (the modulus in the high-density region≥15 MPa, and in the low-density region≥8 MPa), ensuring that it can resist blood flow impact in the blood vessel and can be rapidly cleared through dynamic bond degradation after thrombolysis. In contrast, the passive release mode of Comparative Example 4 (efficiency≤61.8%) is difficult to meet the time window requirements of thrombolytic therapy, and the burst release behavior of Comparative Example 3 may cause the risk of systemic bleeding. These results verify from both positive and negative aspects that the synergistic design of photothermal agents and gradient cross-linking is the physical and chemical basis for realizing efficient and safe drug controlled release.

[0078] Test Example 3: Objective: To verify the effects of low-temperature 3D printing temperature on the retention of dynamic bond activity, printing accuracy, and post-implantation structural stability.

[0079] The experimental steps are as follows: 1. Sample preparation: Prepare scaffold samples (n = 5 for each group) according to the formulations and processes of Examples 1-3 and Comparative Example 6 (printing temperature 25°C).

[0080] Sample structure: double-layer grid (grid spacing in the high-density area is 0.2 mm, and in the low-density area is 0.5 mm).

[0081] 2. Printing accuracy test: Use a scanning electron microscope (SEM, JEOL JSM-7800F) to measure the deviation of the printed line width from the preset value (randomly select 10 points and take the average).

[0082] 3. Detection of dynamic bond activity: Analyze the change in the intensity of the characteristic peaks of dynamic bonds before and after printing by Fourier transform infrared spectroscopy (FTIR, Thermo Nicolet iS50): Borate bond (B-O, 1340 cm -1 ) Schiff base bond (C=N, 1640 cm -1 )

[0083] Calculate the retention rate of dynamic bonds (peak area ratio).

[0084] 4. Evaluation of structure collapse rate: Implant the scaffold into an in vitro simulated blood vessel model (flow rate 150 mL / min). After 24 h, measure the deformation by micro-CT (Skyscan1276) and calculate the collapse rate (deformed volume / initial volume × 100%).

[0085] The experimental results are shown in Table 3: Group Line width deviation (%) Dynamic bond retention rate (%) Collapse rate (%) Key defect Example 1 3.8±0.9 92.5±2.3 2.7±0.5 None Example 2 4.2±1.1 89.8±3.1 3.1±0.8 None Example 3 2.9±0.7 94.2±1.8 1.9±0.3 None Control Example 6 21.5±3.6 68.4±4.7 27.3±2.9 Structural distortion, a large number of dynamic bonds broken From the experimental data in Table 3, it can be obtained that: The low-temperature printing process inhibits the pre-crosslinking reaction of dynamic covalent bonds (borate bonds, Schiff base bonds) by controlling the slurry temperature (8-10°C), ensuring that the polymer chain segments maintain moderate fluidity during the printing process, so as to accurately form complex grid structures (line width deviation in the example ≤ 5%). The relatively high printing temperature (25°C) in Comparative Example 6 accelerates the hydrolysis or recombination of dynamic bonds, resulting in partial breakage of borate bonds during the extrusion process (FTIR peak area decreases by 31.6%). At the same time, the Schiff base bonds undergo irreversible crosslinking due to thermal disturbance, destroying the reversibility of the dynamic network, and ultimately leading to distortion of the printed structure (line width deviation 21.5%) and collapse after implantation (27.3%).

[0086] The retention of the dynamic bond activity is directly related to the long-term stability of the scaffold. In the examples, the dynamic bond still has acid / enzyme responsiveness after printing. After implantation, the reversible breakage-recombination of the bond can be triggered by the local microenvironment to achieve self-repair (the collapse rate ≤ 3.1%); while in Comparative Example 6, the dynamic bond was inactivated due to high-temperature printing, losing the self-repair ability and undergoing irreversible deformation under the impact of blood flow. In addition, low-temperature printing inhibits the aggregation of nanodiamonds (SEM in the examples shows uniform dispersion), maintains its strengthening effect as physical cross-linking points, and further reduces the risk of collapse.

[0087] The experimental results prove from both positive and negative aspects that low-temperature printing is a key parameter for balancing the printability and functionality of the material. Low-temperature conditions (8 - 10 °C) not only ensure the integrity of the dynamic network but also achieve high-precision manufacturing through viscosity regulation; while temperature deviation (such as 25 °C in Comparative Example 6) will disrupt this balance, leading to material failure. This mechanism provides a theoretical basis for the optimization of process parameters and at the same time explains the source of differences in structural stability in clinical applications.

[0088] Test Example 4: Purpose: To verify the regulatory effect of polyaspartic acid on the oriented growth of hydroxyapatite (HA) and the biocompatibility of the scaffold.

[0089] The experimental steps are as follows: 1. Sample preparation: Prepare scaffolds according to the formulations and processes of Examples 1 - 3 and Comparative Example 5 (without polyaspartic acid), and perform mineralization treatment (n = 5 for each group).

[0090] Mineralization conditions: Constant temperature shaker at 37 °C (120 rpm), soak in the mineralization solution for 48 h.

[0091] 2. Analysis of the crystallinity of the mineralized layer: Use an X-ray diffractometer (XRD, Bruker D8 Advance) to scan the mineralized surface (2θ = 25° - 35°), and calculate the preferred orientation degree (Lotgering factor) of the (002) crystal plane.

[0092] 3. Surface bioactivity test: Inoculate MC3T3 osteoblasts (density 1×10 4 cells / cm 2 ) on the surface of the mineralized scaffold. After culturing for 48 h, perform Calcein-AM / PI staining to observe the distribution of live / dead cells, and calculate the cell adhesion rate (the proportion of live cells).

[0093] 4. Determination of the calcium-phosphorus ratio: Use an energy dispersive spectrometer (EDS, Oxford X-MaxN) to analyze the Ca / P molar ratio of the mineralized layer, and randomly select 5 points to take the average value.

[0094] The experimental results are shown in Table 4 as follows: Group (002) Orientation degree (%) Cell adhesion rate (%) Calcium-phosphorus ratio (Ca / P) Key defect Example 1 78.3±3.5 94.2±2.1 1.64±0.05 None Example 2 82.7±2.9 96.5±1.8 1.68±0.07 None Example 3 73.8±4.2 92.7±3.0 1.62±0.06 None Control Example 5 35.4±6.1 72.3±5.4 1.48±0.12 Loose mineralized layer, sparse cell distribution From the experimental data in Table 4, it can be obtained that: The carboxylic acid groups of polyaspartic acid adsorb calcium ions (Ca 2+ ) through electrostatic interaction during the mineralization process, forming a local ion concentration gradient, which induces the preferential growth of hydroxyapatite crystals along the (002) crystal plane, simulating the oriented structure of natural bone tissue. This oriented arrangement not only improves the mechanical strength of the mineralized layer (the degree of orientation in Example (002) ≥ 73.8%), but also promotes the adhesion of osteoblasts by exposing highly bioactive crystal planes (the adhesion rate ≥ 92.7%). In Comparative Example 5, the lack of the templating effect of polyaspartic acid leads to the random stacking of HA crystals (the degree of orientation ≤ 35.4%), forming a loose and porous heterogeneous layer, and the calcium-phosphorus ratio deviates from the bone-like standard, further inhibiting cell proliferation (the adhesion rate ≤ 72.3%).

[0095] The chemical composition and microstructure of the mineralized layer directly affect the long-term biocompatibility of the scaffold. In the examples, the dynamic chelation-release mechanism of polyaspartic acid enables the orderly deposition of Ca 2+ and PO4 3- ions in the mineralization solution, forming a dense and chemically stoichiometrically stable HA layer (Ca / P ≈ 1.65). Its surface micro-nano topological structure matches the osteoblast membrane receptors (such as integrins), activating the cell adhesion signaling pathway (such as FAK phosphorylation). In the mineralized layer of Comparative Example 5, microcracks are generated due to disordered growth (SEM shows that the pore size ≥ 20 μm), resulting in the ineffective anchoring of cell pseudopodia and ultimately leading to cell detachment (the proportion of live cells ≤ 72.3%).

[0096] The experimental results prove from both positive and negative aspects that the introduction of polyaspartic acid is the core of biomimetic mineralization design. Its dual functions (ion guidance and structural stability) ensure that the mineralized layer has both mechanical adaptability and biological activity, while removing this component (Comparative Example 5) will disrupt the mineralization regulation mechanism, resulting in the deterioration of the scaffold performance. This conclusion provides a theoretical basis for the surface functionalization design of materials and reveals the potential reasons for the differences in bone integration effects in clinical applications at the same time.

[0097] Test Example 5: Purpose: To verify the regulation effect of dynamic covalent networks (borate bonds, Schiff base bonds) on the self-healing efficiency and response time of the scaffold.

[0098] The experimental steps are as follows: 1. Sample preparation: Prepare scaffold samples (n = 5 for each group) according to the ratios and processes of Examples 1-3 and Comparative Example 1 (ordinary covalent bonds).

[0099] Sample size: dumbbell shape (ASTM D638 standard, gauge section 10 mm × 2 mm × 1 mm).

[0100] 2. Self-healing efficiency test: Use a blade to cut a notch with a depth of 50% in the center of the gauge section of the sample, and place it in a PBS buffer solution at 37 °C and pH 5.0.

[0101] After 24 h of repair, use a universal material testing machine to test the strength recovery rate after repair (strength after repair / original strength × 100%).

[0102] 3. Determination of repair response time: Immerse the cut sample in a pH 5.0 buffer solution, and record the notch closure time (defined as the time required for the notch width to decrease by 90%) through a microscopic camera (Nikon SMZ25).

[0103] 4. Verification of dynamic bond recombination: Use in-situ infrared spectroscopy (FTIR, Thermo Nicolet iS50) to monitor the change in the characteristic peak intensity of dynamic bonds (B-O, C=N) during the repair process.

[0104] The experimental results are shown in Table 5: Table 5 Comparison of test results of dynamic network and self-healing ability Group Self-healing efficiency (%) Repair response time (min) FTIR dynamic bond recovery rate (%) Key defect Example 1 86.5±4.2 28.3±3.5 89.2±2.8 None Example 2 83.7±5.1 32.1±4.2 85.4±3.6 None Example 3 89.2±3.8 25.8±2.9 91.5±2.1 None Control Example 1 4.2±1.5 > 360 (no repair) 3.1±0.9 No self-healing, crack continues to expand From the experimental data in Table 5, it can be obtained that: The acid-base response characteristics of dynamic covalent bonds are the core driving force for self-healing ability. In a weakly acidic environment (pH 5.0), the borate ester bond (B-O) undergoes reversible hydrolysis-recombination, while the Schiff base bond (C=N) regulates the dynamic exchange rate through protonation-deprotonation. The two work together to achieve dynamic bond recombination at the notch interface (the repair efficiency of the example ≥ 83.7%). In Comparative Example 1, the ordinary covalent bond (glutaraldehyde) lacks dynamic characteristics and cannot be reconstructed after fracture, resulting in the complete loss of self-healing ability (efficiency ≤ 4.2%), which verifies the necessity of the dynamic network design. In-situ infrared spectroscopy further shows that the characteristic peaks (B-O, C=N) of the dynamic bonds in the example have a recovery rate ≥ 85.4% after repair, while the static cross-linked network in Comparative Example 1 has no peak recovery, verifying the mechanism difference at the molecular level.

[0105] The self-healing behavior is directly related to the functional durability of the stent. The rapid response of the dynamic bonds (example repair time ≤ 32.1 min) enables the stent to promptly repair the micro-damages caused by blood flow impact or tissue movement after implantation, avoiding structural failure caused by crack propagation (example collapse rate ≤ 3.1%). In contrast, the irreversible damage accumulation in Comparative Example 1 led to the complete fracture of the stent within 24 h in the in vitro simulation experiment (collapse rate > 25%), demonstrating the crucial role of the dynamic network in long-term stability. In addition, the difference in repair efficiency (Examples 1-3 vs Comparative Example 1) highly matches the clinical requirements. Temporary vascular stents need to maintain functional integrity within 7-10 days, and the dynamic repair precisely covers this time window.

[0106] The experimental results reveal the contribution of the dynamic network to material intelligence from both positive and negative aspects. The chemical design of the dynamic bonds (such as the molar ratio of borate ester to Schiff base) balances the mechanical properties and self-healing ability of the material by regulating the response rate and repair strength. For example, the higher proportion of Schiff base bonds (1:1) in Example 3 increased the repair speed (25.8 min) in an acidic environment but slightly decreased the modulus (16.1 MPa); while the borate ester bond-dominated design (1:3) in Example 2 delayed the response time (32.1 min) but enhanced the stability in a neutral environment. This tunability provides an adaptation solution for different clinical scenarios (such as acute thrombosis and chronic stenosis), and the static network in Comparative Example 1 confirmed its limitations in clinical applications due to its inability to adapt to the dynamic physiological environment.

[0107] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A stent-graft support material for thrombectomy, characterized in that, Comprising components in the following mass percentages: Glycerol polysebacate prepolymer 60 - 70%; Dynamic covalent crosslinking agent 25 - 35%, where the dynamic covalent crosslinking agent is composed of 4-formylphenylboronic acid and hexamethylenediamine in a molar ratio of 1:1 - 3; Carboxylated nanodiamond 5 - 10%; Thermosensitive-photothermal dual-responsive microspheres 3 - 5%, and the microspheres include poly(N-isopropylacrylamide), gold nanorods, and recombinant tissue plasminogen activator.

2. The thrombus extraction stent support material according to claim 1, wherein, The number-average molecular weight of the glycerol polysebacate prepolymer is 10,000 - 15,000.

3. The thrombus extraction stent supporting material according to claim 1, wherein, The particle size of the carboxylated nanodiamond is 10 - 50 nm, and the surface carboxyl density is 5 - 10 μmol / g.

4. The thrombus extraction stent support material according to claim 1, wherein The particle size of the thermosensitive-photothermal dual-responsive microspheres is 10 - 20 μm.

5. The thrombus extraction stent support material according to claim 1, characterized in that In the thermosensitive-photothermal dual-responsive microspheres: The molecular weight of poly(N-isopropylacrylamide) is 50,000 - 100,000, accounting for 70 - 80% of the total mass of the microspheres; The aspect ratio of the gold nanorods is 3:1, and the surface is modified with mercapto groups, accounting for 5 - 8% of the total mass of the microspheres; The drug loading of the recombinant tissue plasminogen activator is 20 - 25 wt%, and the activity is ≥95%.

6. The thrombus extraction stent support material according to claim 5, characterized in that, The thermosensitive-photothermal dual-responsive microspheres are prepared by the following steps: Copolymerize poly(N-isopropylacrylamide) with gold nanorods modified with mercapto groups on the surface to form a thermosensitive-photothermal dual-responsive matrix; Dissolve the recombinant tissue plasminogen activator in the aqueous phase and encapsulate it in the matrix by the emulsion-solvent evaporation method to form drug-loaded microspheres.

7. The preparation process of the stent support material for thrombus extraction according to any one of claims 1-6, characterized in that, Including the following steps: (1) Synthesis of dynamic covalent polymer: Mix the glycerol polysebacate prepolymer, 4-formylphenylboronic acid, and hexamethylenediamine in proportion, react under nitrogen protection for 20 - 24 h, add carboxylated nanodiamond and disperse it by ultrasonic treatment; (2) Loading of thermosensitive microspheres: Add the thermosensitive-photothermal dual-responsive microspheres to the mixture in step (1) and stir and mix at low speed; (3) Low-temperature 3D printing: Extrude and mold the mixed slurry at 8 - 10°C, and adjust the moving speed of the nozzle according to the preset grid density; (4)Light-controlled gradient crosslinking: The printed scaffold is irradiated with ultraviolet light, with the intensity in the high-density area being 50-60 mW / cm 2 , and the intensity in the low-density area being 90-100 mW / cm 2 ; (5) Biomimetic surface mineralization: Immerse the scaffold in a simulated body fluid containing polyaspartic acid for mineralization for 45 - 50 h.

8. The preparation process according to claim 7, characterized in that, In step (4), the ultraviolet light wavelength is 360 - 370 nm, the irradiation time in the high-density area is 25 - 35 s, and the irradiation time in the low-density area is 55 - 65 s.

9. The preparation process according to claim 7, characterized in that, The simulated body fluid described in step (5) contains Na + at 140 - 145 mM, Ca 2+ at 2.4 - 2.6 mM, and the concentration of polyaspartic acid is 0.08 - 0.12%.

10. The preparation process according to claim 7, characterized in that, The preparation process also includes a post-treatment step: Place the scaffold in an environment with a humidity of 85 - 95% and let it stand for 10 - 14 h, and sterilize it with ethylene oxide gas.

Citation Information

Cited By

  • High-diffusion-permeability microsphere and application thereof in three-dimensional cell culture

    CN120923676A

  • Composite porous microsphere capable of self-crosslinking when meeting blood and preparation method of composite porous microsphere

    CN121401482A